Meningkatkan Keaktifan dan Kemampuan Numerasi Melalui Metode Demontrasi dengan Bermain Balok pada Peserta Didik Kelompok B di TK Negeri Pembina Kota Madiun: Improving Activity and Numeracy Skills Through The Demonstration Method Using Blocks for Students in Group B at Pembina State Kindergarten in Madiun City - Agit Handayani; Ibadullah Malawi; Sudarmani (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2026)
This study aims to improve the engagement and numeracy skills of Group B students at TK Negeri Pembina Kota Madiun through the demonstration method using block play. Numeracy skills among Group B students were initially underdeveloped, particularly in recognizing numbers and number symbols, sequencing shapes, and identifying geometric forms. Student engagement—specifically in terms of paying attention to teacher explanations, listening, and answering questions—was also under-developed, showing a lack of interest during learning activities. Therefore, Classroom Action Research  was necessary.The research followed a qualitative approach of the Classroom Action Research type, conducted in two cycles over one month. Each cycle consisted of planning, implementation, observation, and reflection, involving 15 students as research subjects. Data collection techniques included observation and documentation. The data were analyzed using qualitative and descriptive quantitative methods. The results showed an increase in both engagement and numeracy skills from the pre-cycle to Cycle II. The engagement score rose from 67 (pre-cycle) to 76 (Cycle I) and reached 86 in Cycle II. Similarly, numeracy skills increased from 70 (pre-cycle) to 79 (Cycle I) and reached 90 in Cycle II. Based on these results, it can be concluded that the use of the demonstration method through block play can effectively improve the engagement and numeracy skills of Group B students at TK Negeri Pembina Kota Madiun   ABSTRAK Penelitian ini bertujuan untuk meningkatkan keaktifan dan kemampuan numerasi peserta didik kelompok B di TK Negeri Pembina Kota Madiun melalui metode demonstrasi dengan bermain balok. masih belum berkembang peserta didik di Kelompok B kemampuan numerasi dalam mengenal bilangan dan lambang bilangan, mengurutkan bentuk, mengenal bentuk geometri. Keaktifan peserta didik dalam kegiatan di kelas memperhatikan penjelaskan guru, mendengarkan guru dan menjawab pertanyaan guru masih belum berkembang  menunjukkan minat saat kegiatan pembelajaran bermain balok. Untuk itu perlu dilaksanakan penelitian tindakan kelas. Metode demonstrasi yang digunakan dalam kualitatif dengan jenis penelitian Penelitian Tindakan Kelas yang dilaksanakan dalam 2 siklus selama 1 bulan, tiap siklus melalui prosedur perencanaan, pelaksanaan, observasi dan refelksi dengan jumlah subyek penelitian sebanyak 15 peserta didik. Teknik pengumpulan data menggunakan observasi dan dokumentasi. Data yang diperoleh  dianalisis secara kualitatif dan kuantitatif deskriptif.  Hasil penelitian menunjukkan bahwa terdapat peningkatan keaktifan dan kemampuan numerasi pada peserta didik dari prasiklus keaktifan 67, kemampuan numerasi 70, pada siklus I keaktifan 76, kemampuan numerasi 79, pada siklus II keaktifan 86, kemampuan numerasi 90. Dari  hasil tersebut dapat disimpulkan bahwa penggunaan metode demonstrasi melalui bermain balok  dapat meningkatkan keaktifan dana kemampuan numerasi pada peserta didik kelompok B di TK Negeri Pembina Kota Madiun.